Fra alfabet til begrep: Bokmålsordboka og NorNet - Fjeld, Ruth Vatvedt; Knudsen, Rune Lain; Torjusen, Julie M. (Nordiske Studier i Leksikografi, 2012)
This article discusses the use of a monolingual dictionary (Bokmålsordboka) as basis for a wordnet for Norwegian (NorNet). The first part of the article describes the method for constructing the wordnet, and discusses the structure of NorNet with regard to synsets, unique beginners and top ontology. The second part of the article discusses some of the problems that arise due to inconsistencies in the dictionaries, and how these are solved in NorNet. The selection of entries for the wordnet is also discussed. Finally, the article describes plans and future developments. ction of entries to the wordnet is also discussed. Finally, the article accounts for plans and future developments.